1992
DOI: 10.1071/ar9921739
|View full text |Cite
|
Sign up to set email alerts
|

The role of condensed tannins in the nutritional value of mulga (Acacia aneura) for sheep

Abstract: Sheep were fed mulga (Acacia aneura) ad libitum and supplemented with 0, 12 or 24 g/day of polyethylene glycol molecular weight 4000 (PEG), with or without an additional supplement of 1.5 g/day of each of nitrogen (N), phosphorus (P) and sulfur (S) (NPS). Supplementation with either 12 g/day PEG or 24 g/day PEG increased dry matter intake by 56 and 78% respectively and clean wool growth per unit surface area by 166 and 178% respectively. Supplementation with 24 g/day PEG increased wool fibre diameter, linear g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 0 publications
2
26
1
Order By: Relevance
“…The important positive effect of PEG on CP digestibility observed in D2 (+110.8 and 25.19% compared to D0 and D1, respectively) confirmed results of the few earlier studies which dealt with adding PEG to acacia species such as Acacia aneura (Pritchard et al, 1992) and A. cyanophylla (Ben Salem et al, 1996). Tannins in feed can be deactivated by PEG to which they bind more strongly than to protein (Oh et al, 1980).…”
Section: Intake and Digestibilitysupporting
confidence: 75%
See 2 more Smart Citations
“…The important positive effect of PEG on CP digestibility observed in D2 (+110.8 and 25.19% compared to D0 and D1, respectively) confirmed results of the few earlier studies which dealt with adding PEG to acacia species such as Acacia aneura (Pritchard et al, 1992) and A. cyanophylla (Ben Salem et al, 1996). Tannins in feed can be deactivated by PEG to which they bind more strongly than to protein (Oh et al, 1980).…”
Section: Intake and Digestibilitysupporting
confidence: 75%
“…This trend is not consistent with several studies where PEG was shown to improve intake of tannin-rich forages (Pritchard et al, 1992;Silanikove et al, 1996). Ben Salem et al (1996) found that adding PEG (two parts of PEG/one part of tannin) to sheep fed 400 g of barley and acacia foliage ad libitum had no effect on acacia intake.…”
Section: Intake and Digestibilitycontrasting
confidence: 47%
See 1 more Smart Citation
“…Research, 1999, Vol. 42 10% in Lotus pedunculatus and mulga (Acacia aneura) have been shown to reduce VFI in sheep (Barry & Duncan 1984;Waghorn et al 1990;Pritchard et al 1992). However, the relationship between CT concentration and VFI of deer has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing demand for livestock products as a result of rapid growth of population and also for the supply of balanced nutritional food from livestock and feeding the millions and safeguarding their food security will depend on the better utilization of available unconventional feed resources. Many tree seeds contain anti-nutritional factors like polyphenolics and their presence at high level can significantly restrict intake and utilization (Pritchard et al 1992;Kumar, 1992) and also reduce nutritive value of feed (Reed et al 1990). …”
Section: Introductionmentioning
confidence: 99%